Optimising Profits Using the Two-Phase Method and Sensitivity Analysis of UMKM Kedai Ibu - Reynaldy, Faryz; Winarno; Setyawati, Maria Angela Putri; Bernadeta, Deviana Nauli (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2000)
Kedai Ibu is a Micro, Small, and Medium Enterprise (MSME) engaged in home cooking. Business operations run by Kedai Ibu face challenges in determining production optimisation to maximise profits with limited resources, such as raw materials and production time. Optimisation problems often involve two main objectives, namely maximising profits or minimising costs. The research method employed is the two-phase method, with sensitivity analysis conducted through manual calculation and assisted by Lingo software. The purpose of this research is to describe and analyse the implementation of linear programming using the two-phase method to achieve maximum production profit. The research results indicate that the profit obtained is IDR 1,157,000, achieved by producing 250 portions of Ayam Geprek and 50 portions of Ayam Bakar for each order of 300 chicken portions.